Islamic ethical principle of harm prevention (Daf’u al-Darar) and its application in nursing practices - Mohamad Firdaus, Mohamad Ismail; Hashi, Abdurezak Abdulahi; Nurumal, Mohd. Said; Md Isa, Muhammad Lokman (2017)
This is a study of Islamic ethical responses to the moral problems of the nursing profession, particularly, the difficulties related to ethical challenges of harm prevention practices. Nowadays, nurses worldwide are using the ethical theories and models that were developed by the Western scholars to help in the decision-making process. Till now, the knowledge of nursing ethics and Islamic ethics is fragmented, no serious work to integrate between these two. Therefore, this study attempts to integrate these two knowledge into a comprehensive framework.